Implementasi metode cramer menggunakan microsoft excel dalam penyelesaian rangkaian listrik arus searah - Aida, Nur; Verawati, Nenengsih; Pratiwi, Indra; Muttaqin, Khairul (IKIP Siliwangi, 2023)
Direct current electrical circuits are one of the materials studied by students majoring in electrical engineering. To solve electrical circuit problems, students must understand the material on systems of linear equations and matrices. The purpose of this study is to find out what percentage of students apply the Cramer method with the help of Microsoft excel in solving problems of systems of linear equations in direct current electric circuits. This research is qualitative descriptive study. Data collection technique used is the documentation of test results. The subjects of this study were 52 students. First semester of the 2022/2023 academic year, majoring in electrical engineering. The instrument used is a description test of 5 questions, and the results of interviews. Data analysis technique by looking at the effectiveness of using Microsoft Excel in learning a system of linear equations with the Cramer rule method, the results are in the moderate category. To solve the problem of a system of linear equations in direct current circuits as much 62,2% of students it is easier to use the Cramer method and can quickly use Microsoft Excel assistance in calculations, even for many n variabels.